Neural Noise Hypothesis of Developmental Dyslexia. Issue 6 (June 2017) - Hancock, Roeland; Pugh, Kenneth R.; Hoeft, Fumiko
Abstract : Developmental dyslexia (decoding-based reading disorder; RD) is a complex trait with multifactorial origins at the genetic, neural, and cognitive levels. There is evidence that low-level sensory-processing deficits precede and underlie phonological problems, which are one of the best-documented aspects of RD. RD is also associated with impairments in integrating visual symbols with their corresponding speech sounds. Although causal relationships between sensory processing, print–speech integration, and fluent reading, and their neural bases are debated, these processes all require precise timing mechanisms across distributed brain networks. Neural excitability and neural noise are fundamental to these timing mechanisms. Here, we propose that neural noise stemming from increased neural excitability in cortical networks implicated in reading is one key distal contributor to RD. Trends: Increasing evidence from animal work suggests that reading-related risk genes affect cortical excitability and neural noise. Oscillatory models of sensory processing indicate a close link between the regulation of excitation–inhibition cycles and stimulus encoding. We propose neural noise as a distal mechanism in RD that can account for deficits in phonological processing and establishing multisensory grapheme–phoneme mappings through its effects on neural timing.